Financial Development and Employment Structure in China: A VAR-Based Analysis - Wang, Juan; Mohd Radzi, Naziatul Aziah; Saidi, Normaizatul Akma (Asian Journal of Applied Economics, 2025)
This study investigates the relationship between China’s employment structure and financial industry structure, with a focus on their evolution and current dynamics. The objective is to assess how the development of China’s financial sector influences labor distribution across primary, secondary, and tertiary industries, and vice versa. To achieve this, the study employs correlation analysis and a Vector Autoregressive (VAR) model using time-series data from 2000 to 2022. The financial development scale (FIR), financial development structure (FDS), and employment structure (ES) are the key variables. Data were sourced from the China Statistical Yearbook and the China Financial Statistical Yearbook. The empirical findings reveal that while China’s financial development has progressed rapidly—marked by an expanding asset base and diversification—the scale and structure of financial development exert a negative impact on the employment structure in the long term, constraining its advancement. In contrast, improvements in the employment structure positively influence financial development in the short term. Among financial variables, the FDS has a stronger and more sustained effect on employment structure than FIR. The employment structure also exhibits strong self-stability. Based on these results, the study offers policy recommendations in three areas. Financial policy should target the efficient allocation of resources, support employment-intensive sectors, and align financial innovation with labor market needs. Industrial policy should promote closer industry–finance coordination and support the upgrading of traditional sectors to enhance job absorption. Employment policy should prioritize vocational training and strengthen employment services to increase labor adaptability and ensure market stability amid structural shifts.